(untitled) - Dobson, Stephen (New York, 1999)
Policies. ceptionally accessible and fresh approach to economics which will assist and hold the attention of undergraduate students taking subsidiary modules in economics. It is ideal for students following a wide variety of courses who are not going on to specialize in economics. The book assumes no prior knowledge of economics. It is packed with learning aids such as end-of-chapter questions, summaries, lists of key terms, and frequent use of illustrative material. This new book introduces students to some of the key concepts used by economists, and shows how economics can be used to analyse a variety of important social and economic issues. To this end, concepts are often introduced in the context of real world applications, and many of the macroeconomic themes are presented in the context of their historical development. Brevity has been achieved by including only those economic concepts which are the most useful for aiding students' understanding of real events and policies. 'the writing style, the level of the exposition and the structure of the book are all excellent.
Keywords: Economics,Kinh tế học